ASSESSMENT OF HEAVY METAL CONTENTS IN SURFACE WATER OF SELECTED LOCATIONS IN RIVER BHAVANI - K. NAGARAJAN,; R. SIVARAJA., (International Journal of Pharma and Bio Sciences, 2013)
Heavy metals enter into the rivers from variety of sources like mine discharge, run off, chemical weathering of rocks and soils, wet and dry fallout of atmospheric particulate matter and anthropogenic activities. In the present investigation, River Bhavani one of the major rivers in Tamil Nadu, a State in India is chosen and an attempt is made to analyse the river water for heavy metal load determined through surface water analysis. All the analysed metals, Cadmium, Chromium, Copper, Iron, Nickel, Lead, Zinc and Mercury are within the prescribed limits set by Bureau of Indian Standards. However, presence of these heavy metals even in smaller quantities in surface water is a warning signal because the sediments may have higher concentration of these heavy metals. Because heavy metals pollution is less visible but its effects on the ecosystem and humans can be intensive and very extensive when compared to other types of aquatic pollution, concerned authorities should wake up and take steps to contain the quantum of such heavy metals present in surface water.